2016
DOI: 10.1007/s10895-016-1858-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Thermal Stability of Oligofluorene/Rubber Luminescent Blend

Abstract: This paper proposes to obtain homogeneous and stable blends of oligo(9,9-dioctylfluorene)-co-phenylene (OF), a conjugated oligomer with strong tendency of formation of excimers in the solid state, and nitrile rubber (NBR). This rubber protection reduces the formation of polymer excimers in the films. The fluorene oligomer was synthesized via Suzuki reaction and incorporated in the nitrile rubber. The films were formed by spin coating and casting techniques on the proportions of 1, 5, 10, 20 and 50 % (w/w) of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In these situations, the emission spectra are wider and shifted to the red region. It noteworthy that, in general, the addition of 20% or more of conjugated polymer in the blend leads to the formation of aggregates . The results showed that the spectrum with 5 wt% of conjugated polymer was the most appropriate to prepare the blends, as it presents the least amount of aggregates for all polymers studied, without losing the definition of maximums obtained.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In these situations, the emission spectra are wider and shifted to the red region. It noteworthy that, in general, the addition of 20% or more of conjugated polymer in the blend leads to the formation of aggregates . The results showed that the spectrum with 5 wt% of conjugated polymer was the most appropriate to prepare the blends, as it presents the least amount of aggregates for all polymers studied, without losing the definition of maximums obtained.…”
Section: Resultsmentioning
confidence: 93%
“…It noteworthy that, in general, the addition of 20% or more of conjugated polymer in the blend leads to the formation of aggregates. [15] The results showed that the spectrum with 5 wt% of conjugated polymer was the most appropriate to prepare the blends, as it presents the least amount of aggregates for all polymers studied, without losing the definition of maximums obtained. In previous work, the blend emission for PFPh with NBR (50 wt%) was investigated using a blend prepared by Langmuir-Blodgett (LB) technique.…”
Section: Macromolecular Symposiamentioning
confidence: 96%
See 1 more Smart Citation
“…The constant contribution of this band as a function of the PF indicates that residual fluorenone species are not present [41]. Figure 1(b) shows the composition dependence of the integrated area of the resolved components for each FT-IR component labelled as ( 1), ( 2) and (3) as a function of the % polymer content.…”
Section: Mmentioning
confidence: 99%
“…A strategy of incorporating elastomers into light‐emitting conjugated polymers not only enhances deformability but avoids aggregation . An acrylonitrile butadiene rubber (NBR), a polar elastomer, has been used to reduce the formation of excimers in polymers for good chemical and high temperature resistance, which is more suitable for optoelectronic device applications than other elastomers (e.g., styrene butadiene rubber (SBR)) . Nevertheless, elastomeric luminescent materials based on polymer blends with good optical properties under high stretch have not been explored in the literature.…”
Section: Introductionmentioning
confidence: 99%